A hybrid transmission scheme for networked control systems. (January 2020) - Guan, Yanpeng; Peng, Chen
Abstract: Due to its obvious advantage on the efficient use of resources, the event-triggered mechanism is quickly applied in networked control systems (NCSs). However, when some event-triggered data packets are lost during network transmissions, it will become very challenging to analyse the NCSs since two consecutively event-triggered data are internally correlated and the relation will be destroyed when one of the data get lost. With the consideration, this paper proposes a hybrid communication mechanism for NCSs with data loss. Once a measurement that was event-triggered to be released got lost, the following measurements will be instantly transmitted to the controller. A networked controller is obtained for the NCS to guarantee the uniform ultimate boundedness of the system state. Finally, the validness and merits of the developed approach are illustrated through two well studied examples.